Day one : before Hiroshima and after - Wyden, Peter (Simon and Schuster New York, 1985)
Examines the events leading to the creation and use of the atomic bomb.
Keywords: Atomic bomb; World War -- 1939-1945 -- Japan; Bombardment of Hiroshima-shi -- 1945 -- Japan; World War -- 1939-1945; History -- 1912-1945 -- Japan